Characterization of locally connected continua in Euclidean spaces - Oleksiv, I. Ya.; Олексів, І. Я. (Institute of Mathematics, NAS of Ukraine, 1995)
We prove that, for any locally connected bounded continuum in the Euclidean space E n ,n≥2, there exists a sequence of imbeddings of the segment [0, 1] into E n uniformly convergent to a continuous mapping of [0, 1] onto this continuum.